(untitled) (Historia, 2021)
The Chinese in South Africa form one of the country's smallest ethnic minorities, yet from the start of European hegemony their relatively insignificant numbers did not exempt them from the discriminatory impact of the evolving structures of segregation and apartheid. Their colour and cultural heritage gave them a precarious, inconsistent and ambiguous legal status on the periphery of black-white society. This article traces the history of Chinese legal status from the genesis of segregationist policies in the mid-nineteenth century to the abolition of the Population Registration Act a century later as a case study of identity politics. While not escaping the ii.human suffering and degradation of colour legislation, in a sense the Chinese were the first identifiable minority to transcend the apartheid divide and ultimately attain an anomalous position which was neither white nor black. This ambivalence is characteristic of the Chinese encounters with structural discrimination in South Africa.